Akuntansi Pertanggungjawaban dalam Kerangka Syariah: Pendekatan Etis dan Praktis - Salamah, Aulia Nailis; Anwari, Rahmat; Santoso, Anton Bagus; Mafudloh, Kamelia Elima’ana (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
Companies really need responsibility accounting to know the performance of managers through responsibility centers and can help leaders delegate authority and responsibility. Responsibility accounting is a management control tool and is determined through four important aspects, namely assigning responsibilities, creating work measures, evaluating work, and giving awards. This research analyzes sharia accountability accounting with a practical and practical approach. The results show the importance of Islamic principles such as transparency, justice, honesty and trust in sharia accounting. A practical approach involves the use of appropriate accounting methods and techniques, as well as the application of sharia accounting principles. The implication is that companies within the sharia framework need to apply ethical principles and practical approaches to achieve a balance between the interests of individuals, society and the environment. Proper implementation also enables effective performance management and reporting. This research provides an understanding of the importance of sharia responsibility accounting in the context of business based on Islamic principles.